sexpression

s-expression parser

npm install sexpression
var sexpression = require('sexpression');
sexpression.parse('()')
//=> null 
 
sexpression.parse('(1 -2 3.45)')      
//=> [1, -2, 3.45] 
 
sexpression.parse('(a b c)')          
//=> [{ name: 'a' }, { name: 'b' }, { name: 'c' }] 
 
sexpression.parse('(a b (1 2) "a")')  
//=> [{ name: 'a' }, { name: 'b' }, [1, 2], 'a'] 
 
sexpression.parse('(:hoge 1 :fuga 2)')
//=> { hoge: 1, fuga: 2 } 
 
sexpression.parse('(a b :hoge 1 :fuga 2 c)')
//=> [{ name: 'a' }, { name: 'b'}, { hoge: 1, fuga: 2 }, { name: c }] 
 
sexpression.parse('(1 . 2)')
//=> { car: 1, cdr: 2 } 
 
sexpression.parse('((hoge . 1) (fuga . 2))')
//=> [{ car: { name: 'hoge'}, cdr: 1}, { car: { name: 'fuga' }, cdr: 2 }] 
sexpression.stringify([]);           
//=> 'nil' 
 
sexpression.stringify([1, -2, 3.45]) 
//=> '(1 -2 3.45)' 
 
sexpression.stringify([{ name: 'a' }, { name: 'b' }, [1, 2], 'a']) 
//=> '(a b (1 2) "a")' 
 
sexpression.stringify({ car: 1, cdr: 2})  
//=> '(1 . 2)' 
 
sexpression.stringify([{ car: { name: 'hoge'}, cdr: 1}, { car: { name: 'fuga' }, cdr: 2 }])  
//=> '((hoge . 1) (fuga . 2))' 
 
sexpression.stringify({ a: 1, b: 2})                     
//=> '(:a 1 :b 2)' 
 
sexpression.stringify([1, { hoge: 1, fuga: 2 }, "aaa"])  
//=> '(1 (:hoge 1 :fuga 2) "aaa")' 
 
sexpression.stringify({ a: 1, b: 2}, 'alist') 
//=> '(("a" . 1) ("b" . 2))' 
 
sexpression.stringify([1, { hoge: 1, fuga: 2 }, "aaa"], 'alist') 
//=> '(1 (('hoge' . 1) ('fuga' . 2)) 'aaa')' 
 
sexpression.parse('hoge')  //=> { name: 'hoge' } 
sexpression.parse('hoge') instanceof sexpression.Symbol  //=> true 
sexpression.parse('hoge') === sexpression.parse('hoge')  //=> true